Seasonal variation of 200 hPa upper tropospheric features over India in relation to performance of Indian southwest and northeast monsoons (MAUSAM, 2004)
The relation between 200 hPa upper tropospheric parameters such as  temperature, zonal and meridional winds over India with the Indian southwest and northeast monsoons has been studied, based on monthly and seasonal upper air  data of 14 well-distributed Indian radiosonde stations for the 36 year period 1963-98.  It has been found that by and large, positive temperature/height anomalies, negative zonal wind anomalies and northerly position of the sub-tropical ridge during the preceding months/seasons are associated with good southwest/poor northeast monsoons and that complement of the above with poor southwest/good northeast monsoons.  The profiles of the above relationship display a double peak in May and September/October.  A multiple regression forecast scheme for seasonal forecasting of northeast monsoon rainfall, based on October data has been derived which when tested in an independent sample of         5 years yielded nearly 50% correct forecasts.  The southwest monsoon  rainfall of India and the northeast monsoon rainfall of Tamil Nadu/Southern parts of India have been shown to share a negative relationship, though the relationship is discordant rather than decisive, which gets defined better when  years of deficient southwest monsoon  rainfall get excluded. The feature of good Indian northeast monsoon getting preceded by colder upper tropospheric temperatures  as shown in the study tie in well with the accepted mechanism of Asian winter monsoon getting intensified due to cold surges from the Siberian High.